2004
DOI: 10.1016/j.watres.2003.10.027
|View full text |Cite
|
Sign up to set email alerts
|

A model for predicting dissolved organic carbon distribution in a reservoir water using fluorescence spectroscopy

Abstract: A number of water treatment works (WTW) in the north of England (UK) have experienced problems in reducing the dissolved organic carbon (DOC) present in the water to a sufficiently low level. The problems are experienced in autumn/winter when the colour increases and the coagulant dose at the WTW needs to be increased in order to achieve sufficient colour removal. However, the DOC content of the water varies little throughout the year. To investigate this further, the water was fractionated using resin adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…In the study reservoirs, DOC concentrations were similar to those reported in other Mediterranean reservoirs (Marcé et al, 2008), higher than in Asian temperate reservoirs (Kim et al, 2000;Wei et al, 2008) and lower than in European temperate reservoirs (Goslan et al, 2004;Pierson-Wickmann et al, 2010). Among the study reservoirs, the DOC concentration in Cubillas was always higher than in Béznar and Quéntar likely due to its highest catchment area and the ratio of catchment to reservoir area (Table 1).…”
Section: Direct Effects Of Wsoc Deposition On the Reservoir Doc And Cdomsupporting
confidence: 79%
“…In the study reservoirs, DOC concentrations were similar to those reported in other Mediterranean reservoirs (Marcé et al, 2008), higher than in Asian temperate reservoirs (Kim et al, 2000;Wei et al, 2008) and lower than in European temperate reservoirs (Goslan et al, 2004;Pierson-Wickmann et al, 2010). Among the study reservoirs, the DOC concentration in Cubillas was always higher than in Béznar and Quéntar likely due to its highest catchment area and the ratio of catchment to reservoir area (Table 1).…”
Section: Direct Effects Of Wsoc Deposition On the Reservoir Doc And Cdomsupporting
confidence: 79%
“…More recently, TLS has been applied successfully to the study of fluorescent compounds occurring both in dissolved and in stabilized organic matter from various sources and origins [22][23][24][25][26]. Contour maps of HAs isolated for both series at the different stage of composting are shown in Fig.…”
Section: Fluorescence Spectramentioning
confidence: 99%
“…TL spectroscopy Recently, TL spectroscopy has been applied successfully to the study of fluorescent compounds occurring both in dissolved and in stabilized OM (Mobed et al 1996;Chen et al 2002Chen et al , 2003Alberts and Takacs 2004;Goslan et al 2004;Corvasce et al 2006). In particular, TL spectra are the result of merging a series of emission scans from excitations over a range of wavelengths, and allow more detailed information to be obtained, including the number and type of fluorophores present as well as their abundance.…”
Section: Fluorescence Spectroscopymentioning
confidence: 99%